1994
DOI: 10.1038/367572a0
|View full text |Cite
|
Sign up to set email alerts
|

Initial events of myelination involve Fyn tyrosine kinase signalling

Abstract: Myelin is the lipoprotein multimembrane that functions as an insulator preventing the flow of ion currents across the axonal membrane and facilitating the conduction of nerve impulses. It is synthesized by oligodendrocytes in the central nervous system at about the time of birth in mammals. During the initial stages of myelination, several proteins are phosphorylated on tyrosine. Among these proteins, we identified Fyn tyrosine kinase, one of the non-receptor-type tyrosine kinases of the Src family. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
323
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(330 citation statements)
references
References 27 publications
7
323
0
Order By: Relevance
“…Fyn is a member of the Src family of kinases and is associated with cell adhesion, migration, proliferation, differentiation, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999). Increased phosphorylation of Fyn following MAG cross-linking in double-transfected COS cells has been reported previously (Umemori et al, 1994;Umemori et al, 1999). The main site of Fyn autophosphorylation is Tyr418, which leads to activation of kinase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fyn is a member of the Src family of kinases and is associated with cell adhesion, migration, proliferation, differentiation, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999). Increased phosphorylation of Fyn following MAG cross-linking in double-transfected COS cells has been reported previously (Umemori et al, 1994;Umemori et al, 1999). The main site of Fyn autophosphorylation is Tyr418, which leads to activation of kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of an extracellular domain of MAG to apposing molecules on the axonal surface generates an inhibitory signal in the neuron that involves p75, RhoA and Rac1 signaling (Niederost et al, 2002;Wang et al, 2002). In addition, intracellular domains of MAG bind to microtubules (Kursula et al, 2001) and Fyn tyrosine kinase (Umemori et al, 1994;Umemori et al, 1999) in OLs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fyn is essential for myelin development in the central nervous system (CNS) and mediates learning and memory. 13,14,28,29 Conceivably, fyn-mediated PIKE-A phosphorylation might regulate its biological functions in the brain. In summary, our data provide compelling evidence that active fyn is a physiological tyrosine kinase for PIKE-A.…”
Section: Discussionmentioning
confidence: 99%
“…8 Src kinases are activated by a variety of cell surface receptors, G-protein-coupled receptors 10 and by growth factor receptor stimulation. 11 Fyn, a critical member of src family tyrosine kinase, mediates a variety of cellular processes, including signaling via the T-cell receptor, 12 regulation of brain function 13,14 as well as adhesion-mediated signaling. 15,16 It is worth noting that src tyrosine kinases including fyn also mediate cell survival.…”
mentioning
confidence: 99%
“…Fyn, a member of the Src family of kinases, has been reported to play a key role in regulating OPC proliferation and differentiation [41][42][43]. In primary cultured OPCs, we found that both P2X7 receptors and Fyn were expressed in OPCs (Fig.…”
Section: P2x7 Receptors Interact With Fyn In Cultured Opcsmentioning
confidence: 68%